EFEKTIVITAS PAIKEM GEMBROT MELALUI MEDIA WAYANG UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Rahmawati, Fita; Mashar, Riana; Mahardika, Astuti (Universitas Muhammadiyah Magelang, 2014)
The research is supposed toknow applying Paikem Gembrot Approach using wayang to improve student’s ability in sains’learning in Ar Risalah Islamic Elementary School Secang. Type of this research is Classroom Action Research (CAR) that was adapted from Kemmis and Mc Taggart model with two cycle. Every cycle consisted of planning, acting, observation and reflection. Subject of the reseacrh are students of Ar Risalah Islamic Elementary School in grade III about 29 students.Technique of collecting data are test, observation and documentation. Result of the research had shown that Paikem Gembrot Approach using wayang gave positif effect for increasing score and ability in Sains’Learning. That was prove from the averrage of Sains score, it was increasing in every cycle. Score of the students before treatment about 62, 93 with the percentage 24,13%. In cycle I it was increasing became 74,48 with the percentage 58, 62%. In cycle II there was significant increasing became 89, 65%. Based on result of the research, it was concluded that with applying Paikem Gembrot Approach using Wayang can increase result in Sains’Learning with the discussion about the way to conserve the natural environment in grade III Ar Risalah Islamic Elementary School Secang.